PROJECT STATUS REPORT AS REPORTED ON 11/15 (Tufts Archival Research Center, 2007)
Confidential; Incomplete; Project Status Report for November 1985. Lists each project name and the staff members associated with the project. Includes the following topics: fire safety program, labor relations, airline smoking, media relations, state excise tax increases, and indoor air quality.